Variability of cut‐off values for the detection of lupus anticoagulants: results of an international multicenter multiplatform study. (18th April 2017) - Tripodi, A.; Chantarangkul, V.; Cini, M.; Devreese, K.; Dlott, J. S; Giacomello, R.; Gray, E.; Legnani, C.; Martinuzzo, M. E.; Pradella, P.; Siegemund, A.; Subramanian, S.; et al.
Abstract : Essentials Between‐lab variations of cut‐off values in lupus anticoagulant detection are unknown. Cut‐off values were calculated in 11 labs each testing plasma from 120 donors with 3 platforms. Major variation was observed even within the same platform. Cut‐off values determined in different labs are not interchangeable. Summary: Background: Cut‐off values for interpretation of lupus anticoagulant (LA) detection are poorly investigated. Aims: (i) To assess whether results from healthy donors were normally distributed and (ii) the between‐laboratories differences in cut‐off values for screening, mixing and LA confirmation when calculated as 99th or 95th centiles, and (iii) to assess their impact on the detection rate for LA. Methods: Each of 11 laboratories using one of the three widely used commercial platforms for LA detection was asked to collect plasmas from 120 healthy donors and to perform screening, mixing and LA confirmation with two methods (activated partial thromboplastin time [APTT] and dilute Russell viper venom [dRVV]). A common set of LA‐positive or LA‐negative freeze‐dried plasmas was used to assess the LA detection rate. Results were centralized (Milano) for statistical analysis. Results and conclusions: (i) Clotting times or ratios for healthy subjects were not normally distributed in the majority of cases. The take‐home message is that cut‐off values should be determined preferably by the non‐parametric method based on centiles. (ii) There were relatively large inter‐laboratory cut‐off variations even within the same platform and the variability was marginally attenuated when results were expressed as ratios (test‐to‐normal pooled plasma). The take‐home message is that cut‐off values should be determined locally. (iii) There were differences between cut‐off values calculated as 99th or 95th centiles that translate into a different LA detection rate (the lower the centile the greater the detection rate). The take‐home message is that cut‐off values determined as the 95th centile allow a better LA detection rate.